(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
The nonradical quasi-formulations of a Leibniz algebra are maxima of Leibniz algebras. The article describes Leibniz differential algebras, which are quasi-forms of the first and second types. The nilradials of the first and second types are quasi-forms of the maximum in the Leibniz algebra.